Analysis of the Accuracy of Interpolation of Entire Operators in a Hilbert Space in the Case of Perturbed Nodal Values - Kashpur, O. F.; Khlobystov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
In a Hilbert space with Gaussian measure, we obtain an estimate for the accuracy of interpolation of an entire operator in the case where its values are perturbed at nodes and determine the value of the degree of an interpolation polynomial the exceeding of which does not improve the estimate of the accuracy of interpolation.